2022
DOI: 10.3390/cells11091564
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences Predict the Phenome of Affective Disorders and These Effects Are Mediated by Staging, Neuroimmunotoxic and Growth Factor Profiles

Abstract: Adverse childhood experiences (ACEs) enhance pro-inflammatory and pro-oxidant responses. In affective disorders, recent precision nomothetic psychiatry studies disclosed new pathway phenotypes, including an ROI—reoccurrence of illness (ROI)—oxidative stress latent construct. The aim of the present study is to delineate a) whether ACEs sensitize the M1 macrophage, the T helper cells (Th)1, Th2, and Th17, the IRS (immune-inflammatory-responses system), the CIRS (compensatory immunoregulatory system), and the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(121 citation statements)
references
References 86 publications
3
118
0
Order By: Relevance
“…Thus, it is preferable to thoroughly investigate the TRP and TRYCATs in drug-naïve patients with a first episode or to control statistically for the medication status. Moreover, future research should stratify patients according to the staging phases of affective disorders since disease staging is related to greater neurotoxicity (Maes, Moraes et al 2019, Maes, Rachayon et al 2022). Fourth, a considerable number of studies seemed to have been conducted without correcting for major confounding variables such as smoking and alcoholism and their effects on TRP (Badawy 2002) and TRYCAT (Leclercq, Schwarz et al 2021) metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is preferable to thoroughly investigate the TRP and TRYCATs in drug-naïve patients with a first episode or to control statistically for the medication status. Moreover, future research should stratify patients according to the staging phases of affective disorders since disease staging is related to greater neurotoxicity (Maes, Moraes et al 2019, Maes, Rachayon et al 2022). Fourth, a considerable number of studies seemed to have been conducted without correcting for major confounding variables such as smoking and alcoholism and their effects on TRP (Badawy 2002) and TRYCAT (Leclercq, Schwarz et al 2021) metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the activated IRS pathways in affective disorders are associated with activation of nitro-oxidative pathways with increased reactive oxygen and nitrogen species (RONS), and consequent lipid peroxidation and protein oxidation (Maes, Galecki et al 2011, Maes 2022). Activation of IRS and nitro-oxidative pathways are associated with the key features of affective disorders, including severity of illness, staging (reoccurrence of episodes) and suicidal behaviors including suicidal ideation and attempts (Vasupanrajit, Jirakran et al 2021, Maes 2022, Maes, Rachayon et al 2022). The current theory is that the neurotoxic effects of M1 and Th-1 cytokines and RONS cause neuro-affective toxicity with dysfunctions in brain connectome pathways that lead to staging and the phenome of MDD/BD (Maes 2022, Maes, Rachayon et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The interrelationships among the PSST affective symptoms of PMS and perinatal depressive symptoms and the effects of ACEs may be explained by the effects of adverse outcome pathways. Thus, there is evidence that a) PMS (or better MCAS) and menstrual distress are in part due to immune-inflammatory processes (Roomruangwong and Maes, 2021); b) major depression and perinatal depression are associated with activated immune-inflammatory pathways; and c) ACEs induce an immune-inflammatory and growth factor response which is a major determinant of the phenome of depression (Maes et al, 2022). Moreover, psychosocial stressors including relation dissatisfaction and abuse by the partner during pregnancy may further exacerbate those immune-inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that adverse childhood experiences (ACEs) are strongly associated with the onset of AD (Abe et al, 2021), major depressive disorder (Maes et al, 2019; Maes et al, 2022), and possibly premenstrual syndrome (PMS) (Jacobs et al, 2015; Yang et al, 2022). Such findings suggest that ACEs may underlie the association between PMS and AD.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that ACEphem and a family history of mood disorders are significant predictors of ROI. Previous research has shown that ROI is strongly predicted by gene (paraoxonase 1 or PON1 Q192R gene) X ACE interactions and the resulting deficits in PON1-high density lipoprotein (HDL) cholesterol complex (Maes et al, 2018; 2019), as well as with an increased immune and growth factor responsiveness in unipolar depression (Maes et al, 2022b), and dysfunctional T regulatory activities in bipolar disorder (Maes et al, 2021b). Interestingly, the frequency of seizures (kindling) in temporal lobe epilepsy is related with oxidative pathways and decreased antioxidant defenses, particularly PON1 activity and sulfhydryl groups (Maes et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%